Poesia Concreta em Dora Ferreira da Silva - Saramago, Rogélia Mundim (2017)
Abstract: Dora Ferreira da Silva, winner of several significant awards in the literary world, has a unique and peculiar style. Through her verses, one can immerse himself in both sacred and profane worlds. Known for her intimate poetry of metaphysical reverberations, influenced by the inwardness of Rainer Maria Rilke and Jung’s ideas of archetype, unconscious and symbol, Dora writes her poems with such subtlety and emphasis on the primordial, elementary beauty with impeccable language. Her lyricism is permeated by the images and universal symbolisms of myths, which are part of daily life and religiosity, while it evokes images in the collective unconscious, awakening to the ancestry of man. However, Dora Ferreira da Silva manages to deal with these themes in a style which is apparently opposite to the lyric subjectivity of her poetry – Concretism. In this aspect, the proposal of this Master’s dissertation consists in analyzing Dora's poetry focusing on two corpura – “Lunimago” and “Elementária” –, both from her first opus, An-danças, which was published in 1970. In this set of poems, the experimentation carried out by the poet in the paths proposed by the Concrete Poetry is analyzed and evidenced, within the context of Brazilian Modernism. The fundamentals of the theoretical contribution of myth criticism, as well as the theoretical assumptions of critics and scholars of poetry and concretism are used. At this stage in the poet’s work her style is emphasized in the use of mythical images allied to verbal, sonorous and visual forms, characteristic of concretism, which represents the central theme of this dissertation and draws attention to it since it is still unknown and rarely mentioned.